D. Francisco Manuel De Melo E O Barroco Peninsular 2010
DOI: 10.14195/978-989-26-0245-5_11
|View full text |Cite
|
Sign up to set email alerts
|

D. Francisco Manuel de Melo, historiador

Abstract: A navegação consulta e descarregamento dos títulos inseridos nas Bibliotecas Digitais UC Digitalis, UC Pombalina e UC Impactum, pressupõem a aceitação plena e sem reservas dos Termos e Condições de Uso destas Bibliotecas Digitais, disponíveis em https://digitalis.uc.pt/pt-pt/termos.Conforme exposto nos referidos Termos e Condições de Uso, o descarregamento de títulos de acesso restrito requer uma licença válida de autorização devendo o utilizador aceder ao(s) documento(s) a partir de um endereço de IP da insti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 2 publications
0
4
0
3
Order By: Relevance
“…The frequency independent part corresponds to the free charge carrier transport and the frequencydispersed portion reflects the response of the bound charges. Now as the temperature increases, the thermally activated charge carriers participate more and more to the transport and as a result the frequency up to which the limiting dc value prevails extends along with decrease in the impedance of the nanocomposites [24,61,62]. The presence of two regions is also manifested in the Z 00 versus f graphs where a broad relaxation peak appears which shifts towards higher frequencies with increase in temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency independent part corresponds to the free charge carrier transport and the frequencydispersed portion reflects the response of the bound charges. Now as the temperature increases, the thermally activated charge carriers participate more and more to the transport and as a result the frequency up to which the limiting dc value prevails extends along with decrease in the impedance of the nanocomposites [24,61,62]. The presence of two regions is also manifested in the Z 00 versus f graphs where a broad relaxation peak appears which shifts towards higher frequencies with increase in temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Dielectric characteristics of Methyl orange (MO)/polyvinyl alcohol films were studied by Oliveira and de Melo [24] in the temperature range 294 K to 370 K and they observed that incorporation of the methyl orange aggregation in the matrix enhances the effective charge transport and affects the dielectric properties significantly. They have found that electrical properties of the polymeric films can also be altered by incident light, based on which they had proposed that this PVA composite can be considered in designing solid state memory devices.…”
Section: Introductionmentioning
confidence: 99%
“…Eqs. (85)(86)(87)(88)(89)(90)(91)(92)(93)(94)(95)(96) constitute non-perturbative constraints on the fermion-photon vertex: for every Ansatz for the Yfunctions, the resulting function W is restricted to guarantee the integral constraint (85), so that the MR of the fermion propagator is ensured. To bring out the applicability and scope of the integral constraint on the massless Y -functions, Eq.…”
Section: Mr Constraintsmentioning
confidence: 99%
“…Therefore, physically meaningful truncations of QCD's SDEs demand incorporation of DCSB through the relevant Green functions, in particular the quark propagator and the quark-gluon vertex. Regarding the latter, valuable progress has been made both in lattice, [85][86][87][88][89][90][91] and continuum studies. However, due to the non-abelian nature of QCD, investigating the impact of DCSB on the quark-gluon vertex, and vice versa, from the first principles, is still a theoretical challenge.…”
Section: Introductionmentioning
confidence: 99%
“…1. Observou-se uma perda de massa contínua entre a temperatura ambiente e 900 ºC, atribuída à eliminação de água adsorvida e à decomposição dos aminoácidos presentes na estrutura orgânica da gelatina [17]. As amostras apresentaram pequenas quantidades de perda de massa, sendo 5,3% e 5% para os pós CoCr 2 O 4 e Co x Zn 1-x Cr 2 O 4 , respectivamente.…”
Section: Resultsunclassified